Antismoking agents do not contribute synergistically to semaglutide’s ability to reduce alcohol intake in rats - Aranäs, Cajsa; Blid Sköldheden, Sebastian; Jerlhag, Elisabet (Frontiers in Pharmacology, 2023)
Preclinical studies have identified glucagon-like peptide-1 receptor (GLP-1R) agonists, and the antismoking agents varenicline and bupropion as tentative agents for treatment of alcohol use disorder (AUD). Combining different medications is a recent approach that has gained attention regarding heterogenous and difficult-to-treat diseases, like AUD. Successfully, this approach has been tested for the combination of varenicline and bupropion as it prevents relapse to alcohol drinking in rats. However, studies assessing the effects of the combination of semaglutide, an FDA-approved GLP-1R agonist for diabetes type II, and varenicline or bupropion to reduce alcohol intake in male and female rats remains to be conducted. Another approach to influence treatment outcome is to combine a medication with feeding interventions like high fat diet (HFD). While HFD reduces alcohol intake, the ability of the combination of HFD and semaglutide to alter alcohol drinking is unknown and thus the subject for a pilot study. Therefore, three intermittent alcohol drinking experiments were conducted to elucidate the effectiveness of these treatment combinations. We show that semaglutide, bupropion or HFD reduces alcohol intake in male as well as female rats. While various studies reveal beneficial effects of combinatorial pharmacotherapies for the treatment of AUD, we herein don’t report any additive effects on alcohol intake by adding either varenicline or bupropion to semaglutide treatment. Neither does HFD exposure alter the ability of semaglutide to reduce alcohol intake. Although no additive effects by the combinatorial treatments are found, these findings collectively provide insight into possible monotherapeutical treatments for AUD.